Permethrin-Treated Clothing as Protection against the Dengue Vector, Aedes aegypti: Extent and Duration of Protection - DeRaedt Banks, Sarah (2016)
Introduction: Dengue transmission by the mosquito vector, Aedes aegypti, occurs indoors and outdoors during the day. Personal protection of individuals, particularly when outside, is challenging. Here we assess the efficacy and durability of different types of insecticide-treated clothing on laboratory-reared Ae. aegypti.